Rememory [videorecording (DVD)] - Palansky, Mark; Dinklage, Peter; Ormond, Julia; Donovan, Martin, 1957- (Lions Gate Entertainment, 2017)
Gordon Dunn, a visionary scientific pioneer, is found dead shortly after he unveils his newest work: a device able to extract, record, and play a person's memories. Soon, a mysterious man shows up at his widow's door, claiming to be a friend of her late husband. After stealing the machine from the house, the man uses it to try and solve the mystery of Gordon's death, beginning an investigation on memories that leads him to unexpected and dangers places.